The hepatic AMPK-TET1-SIRT1 axis regulates glucose homeostasis - Chunbo Zhang (eLife Sciences Publications Ltd, 2021)
Ten-eleven translocation methylcytosine dioxygenase 1 (TET1) is involved in multiple biological functions in cell development, differentiation, and transcriptional regulation. Tet1 deficient mice display the defects of murine glucose metabolism. However, the role of TET1 in metabolic homeostasis keeps unknown. Here, our finding demonstrates that hepatic TET1 physically interacts with silent information regulator T1 (SIRT1) via its C-terminal and activates its deacetylase activity, further regulating the acetylation-dependent cellular translocalization of transcriptional factors PGC-1α and FOXO1, resulting in the activation of hepatic gluconeogenic gene expression that includes PPARGC1A, G6PC, and SLC2A4. Importantly, the hepatic gluconeogenic gene activation program induced by fasting is inhibited in Tet1 heterozygous mice livers. The adenosine 5’-monophosphate-activated protein kinase (AMPK) activators metformin or AICAR—two compounds that mimic fasting—elevate hepatic gluconeogenic gene expression dependent on in turn activation of the AMPK-TET1-SIRT1 axis. Collectively, our study identifies TET1 as a SIRT1 coactivator and demonstrates that the AMPK-TET1-SIRT1 axis represents a potential mechanism or therapeutic target for glucose metabolism or metabolic diseases.